Efforts to Develop Cognitive Abilities in Children Aged 4-5 Years Using Number Wheel Media at Cahaya Utara PAUD Pawangdesa Gunjan Asri - Denda, Denda; Kertadi, Kertadi; Julianti, Martina; Muhamad, Idris (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This research aims to discuss how to improve children's cognitive development by playing with number pinwheels for students in the group (4-5) years old at Cahaya Utara Pawang PAUD. The type of observation that we used in this research was (PTK) Classroom Action Research using 2 cycles, in each cycle we held 3 meetings, the students we studied were 11 children where these participants were group A. The technique used in this research used observation and documentation Research is carried out in a systematic, empirically reflective and rational manner regarding every action that has been carried out during the research. Meanwhile, in this research, data analysis was carried out using an analysis model consisting of: Planning, Implementation, Observation and reflection. The results of research at Cahaya Utara Pawang preschool in cognitive development using number wheel media are very important because in learning activities in kindergarten an educator must be imaginative and have the ability to create a fun teaching and learning atmosphere so that students do not get bored quickly in learning. Kindergarten is an institution that is very important in developing children's cognitive abilities. As we know, this age is a golden age and will not happen again, therefore an educator must pay very careful attention.